2021
DOI: 10.21608/assjm.2021.186316
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genotypes, Season of Birth, Parity Order and the Interactions between Them on Litter Traits and Body Weight Measurements of Rabbits

Abstract: The aim of current study was to investigate the effects of the effect of genotype, season of birth and parity order on litter traits and body weight measurements of V-line and Moshtohor line (M-line) of rabbits. A total number of six thousand and three hundreds (6300 kits) offspring obtanid from these strains (100 sires and 300 dams) were used in this study. The body weight traits were recorded at 4, 8 and 12 weeks of age. Litter size at birth (LSB), Litter size at weaning at 28 days postnatal (LSW), Litter we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…On the other hand, the drop in LS at the 3 rd week and at weaning in model 2 may be attributed to the impact of various environmental factors on lactation capacity and mothering ability because of hypothermia. These results agree with the findings of Desouky (2021);El-Ratel et al (2023). The increase in P4 was accompanied by the increase in LS (Ashour and Abdel-Rahman, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the drop in LS at the 3 rd week and at weaning in model 2 may be attributed to the impact of various environmental factors on lactation capacity and mothering ability because of hypothermia. These results agree with the findings of Desouky (2021);El-Ratel et al (2023). The increase in P4 was accompanied by the increase in LS (Ashour and Abdel-Rahman, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Desouky et al, (2021), who found extremely significant (P < 0.05) changes in body weight across age intervals; this is the finding i obtained. The third parity had the heaviest body weight at 4, 8, and 12 weeks, and body weight gain at 4-8, 8-12 and 4-12 weeks respectively.…”
supporting
confidence: 66%